The Impact of Gamified Learning Environments on Social Collaboration and Student Motivation in Education - Astri Chintya Astana; Trifena Ruth Clara; Parshuram Sahoo (International Forum of Researchers and Lecturers, 2025)
This study aims to assess the impact of gamification on students' motivation and social collaboration in the educational environment. The problems identified were the low levels of motivation and collaboration in traditional learning methods. The aim of this study is to explore whether the application of gamification can improve both aspects. The methods used were experimental design with control groups and experiments, as well as the application of gamification class activities that included elements such as point systems, levels, and collaborative tasks. The main results showed that the experimental group experienced a significant increase in motivation and social collaboration compared to the control group. The average motivation score increased from 3.2 to 4.1, and the collaboration score increased from 3.0 to 4.0. These findings are in line with previous research that showed that gamification can increase student engagement through elements of games. In conclusion, gamification is an effective approach to increase students' motivation and social collaboration in learning.